Letter: Incidence of endometrical carcinoma. - Doll, R; Kinlen, L; Skegg, D (1976)
The authors respond to a communication criticizing an earlier article of theirs published in the British Medical Journal, April 3, 1976. They were accused of incorrectly interpreting data on mortality rates for cancer of the corpus uteri, in Wales and England, as evidence that no increase in the incidence of endometrial cancer had occurred. The authors point out that they drew no such conclusion from the mortality rates. Included in the letter are some recent data from Great Britain on the incidence of endometrial cancer and the prescribing of estrogens. among the age groups 40-49, 50-59, 60-69, and 70-79, the % of women who received 1 or more prescriptions were 4.6, 5.9, 1.1, and 1.0, respectively. In view of these low prescription rates, the lack of increase in the incidence of endometrial cancer, up to 1973, and in the mortality from endometrial cancer, up to 1974, in England and Wales is not surprising, nor can this data be used to support or deny an association between the incidence of endometrial cancer and prescribed use of estrogens.